The Role of Oxidative Stress in the Aging Heart - Pagan, Luana U. [UNESP]; Gomes, Mariana J.; Gatto, Mariana [UNESP]; Mota, Gustavo A. F. [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina P. [UNESP] (MDPI, 2022)
Medical advances and the availability of diagnostic tools have considerably increased life expectancy and, consequently, the elderly segment of the world population. As age is a major risk factor in cardiovascular disease (CVD), it is critical to understand the changes in cardiac structure and function during the aging process. The phenotypes and molecular mechanisms of cardiac aging include several factors. An increase in oxidative stress is a major player in cardiac aging. Reactive oxygen species (ROS) production is an important mechanism for maintaining physiological processes; its generation is regulated by a system of antioxidant enzymes. Oxidative stress occurs from an imbalance between ROS production and antioxidant defenses resulting in the accumulation of free radicals. In the heart, ROS activate signaling pathways involved in myocyte hypertrophy, interstitial fibrosis, contractile dysfunction, and inflammation thereby affecting cell structure and function, and contributing to cardiac damage and remodeling. In this manuscript, we review recent published research on cardiac aging. We summarize the aging heart biology, highlighting key molecular pathways and cellular processes that underlie the redox signaling changes during aging. Main ROS sources, antioxidant defenses, and the role of dysfunctional mitochondria in the aging heart are addressed. As metabolism changes contribute to cardiac aging, we also comment on the most prevalent metabolic alterations. This review will help us to understand the mechanisms involved in the heart aging process and will provide a background for attractive molecular targets to prevent age-driven pathology of the heart. A greater understanding of the processes involved in cardiac aging may facilitate our ability to mitigate the escalating burden of CVD in older individuals and promote healthy cardiac aging.
Keywords: Aged heart; Cardiac metabolism; Cardiac remodeling; Reactive oxygen species; Senescence